1993
DOI: 10.1007/bf01246360
|View full text |Cite
|
Sign up to set email alerts
|

Basement membranes during development of human nerve: Schwann cells and perineurial cells display marked changes in their expression profiles for laminin subunits and ?1 and ?4 integrins

Abstract: The formation of the connective tissue compartments of human sciatic and tibial nerves was studied with special reference to the maturation of the basement membranes during foetal development (11-35 weeks of gestation). All Schwann cells were surrounded by continuous basement membranes as early as at week 11, while the perineurial cells became covered by basement membranes gradually between weeks 17 and 35, as estimated by electron microscopy. The first laminin subunits detectable within the nerve were the B1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 37 publications
2
47
1
Order By: Relevance
“…Our data are consistent with a requirement for integrin-dependent signaling pathways in the induction of schwannoma phenotypes. Schwann cells express speci®c matrix-binding integrins that are required for establishment of Schwann cell polarity and myelination (Einhaber et al, 1993;Feltri et al, 1994;Fernandez-Valle et al, 1994Jaakkola et al, 1993). We predict, therefore, that schwannoma cells should abnormally ensheath axons and should fail to establish polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with a requirement for integrin-dependent signaling pathways in the induction of schwannoma phenotypes. Schwann cells express speci®c matrix-binding integrins that are required for establishment of Schwann cell polarity and myelination (Einhaber et al, 1993;Feltri et al, 1994;Fernandez-Valle et al, 1994Jaakkola et al, 1993). We predict, therefore, that schwannoma cells should abnormally ensheath axons and should fail to establish polarity.…”
Section: Discussionmentioning
confidence: 99%
“…So far, however, all laminin chains sequenced resemble either A, B1, or B2, and all of the laminins purified are trimers containing an A-like, a B1-like, and a B2-like chain (6, 19 -22). Based on these findings, a new nomenclature has been adopted in which laminin chains are divided into ␣ (A-like), ␤ (B1-like) and ␥ (B2-like) subfamilies; A, M, B1, S, and B2 are now called ␣1, ␣2, ␤1, ␤2, and ␥1, respectively (6).Consistent with laminin's trimeric structure, all basal laminae characterized to date contain at least one ␤ and at least one ␥ chain (19,20,(23)(24)(25)(26)(27)(28). For the ␣ chains, on the other hand, the situation is less clear.…”
mentioning
confidence: 99%
“…Perineurial cells of the perineurium form a selective diffusion barrier between the endoneurium and the epineurium (Thomas 1963;Jaakkola et al 1993;Pummi et al 2004), and we have previously shown that the tight junction (TJ) proteins zonula occludens (ZO)-1, occludin, claudin-1, and claudin-3 all contribute to the formation of this perineurial diffusion barrier in human peripheral nerves (Pummi et al 2004). In epithelia and endothelia, TJs form physical barriers and regulate the paracellular transport of ions, water, and other small molecules by discriminating sizes and charges (Anderson 2001;Hartsock and Nelson 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The non-compact structures include the paranodal loop regions, the Schmidt-Lanterman incisures, the periaxonal cytoplasmic collar, and the inner and outer mesaxons. At the nodes of Ranvier, interdigitations of the plasma membranes of adjacent Schwann cells assure the continuity of the Schwann cell sheath along the whole length of the axon, while a continuous, Schwann cell-derived basal lamina forms a permeable boundary between the endoneurial connective tissue layer and the Schwann cell myelin sheath (Thomas 1963).Perineurial cells of the perineurium form a selective diffusion barrier between the endoneurium and the epineurium (Thomas 1963;Jaakkola et al 1993;Pummi et al 2004), and we have previously shown that the tight junction (TJ) proteins zonula occludens (ZO)-1, occludin, claudin-1, and claudin-3 all contribute to the formation of this perineurial diffusion barrier in human Correspondence to: Sirkku Peltonen, …”
mentioning
confidence: 99%
See 1 more Smart Citation